2016
DOI: 10.1371/journal.pone.0161391
|View full text |Cite
|
Sign up to set email alerts
|

Altered Diastolic Flow Patterns and Kinetic Energy in Subtle Left Ventricular Remodeling and Dysfunction Detected by 4D Flow MRI

Abstract: Aims4D flow magnetic resonance imaging (MRI) allows quantitative assessment of left ventricular (LV) function according to characteristics of the dynamic flow in the chamber. Marked abnormalities in flow components’ volume and kinetic energy (KE) have previously been demonstrated in moderately dilated and depressed LV’s compared to healthy subjects. We hypothesized that these 4D flow-based measures would detect even subtle LV dysfunction and remodeling.Methods and ResultsWe acquired 4D flow and morphological M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 24 publications
6
63
0
Order By: Relevance
“…Multiple 4D flow MRI studies showed that patients with LV dysfunction present altered flow patterns through the LV with impaired preservation of inflow KE to the end of diastole and altered KE-time curves (the amount of KE inside the LV during each time step over the total cardiac cycle) [4,6,7,21], even in patients with normal to mild LV remodeling and normal to mildly depressed LV systolic function [7]. These KE changes in the LV could be a valuable diagnostic marker to evaluate diastolic function and might be useful for early detection of deteriorating ventricular function [1, 4-7, 21, 22], which could reduce patient morbidity and mortality [23].…”
Section: Kinetic Energy (Ke) Over LV Diastolementioning
confidence: 99%
See 2 more Smart Citations
“…Multiple 4D flow MRI studies showed that patients with LV dysfunction present altered flow patterns through the LV with impaired preservation of inflow KE to the end of diastole and altered KE-time curves (the amount of KE inside the LV during each time step over the total cardiac cycle) [4,6,7,21], even in patients with normal to mild LV remodeling and normal to mildly depressed LV systolic function [7]. These KE changes in the LV could be a valuable diagnostic marker to evaluate diastolic function and might be useful for early detection of deteriorating ventricular function [1, 4-7, 21, 22], which could reduce patient morbidity and mortality [23].…”
Section: Kinetic Energy (Ke) Over LV Diastolementioning
confidence: 99%
“…4D flow MRI has recently emerged as a novel tool for in vivo quantification of intracardiac flow energetics, associated energy losses and vortical flow patterns by means of kinetic energy (KE) [4][5][6][7], viscous energy loss (EL) [1] and vorticity [8,9]. KE is the energy contained in the flow of the bloodstream due to motion and EL is the KE that is irreversibly lost due to viscosity-induced frictional forces within the blood flow [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In myopathic LVs, reduced volume and pre-systolic KE of the Direct Flow has been demonstrated compared to normal LVs (62,91). The inflowing Direct Flow proceeds deeper into the LV chamber and interacts more with blood already residing in the LV.…”
Section: Flow Analysis In Failing Hearts With and Without Lbbb (Paper Iii)mentioning
confidence: 99%
“…This inefficient flow of blood through the heart may influence diastolic wall stress, and thus, contribute to further myocardial remodeling. Furthermore, the altered diastolic flow routes and impaired preservation of pre-systolic KE have been demonstrated in compensated heart failure patients with mildly remodeled LVs compared to normal LVs despite similar LV stroke volume (91).…”
Section: Physiological Considerationsmentioning
confidence: 99%